2000
DOI: 10.1207/s15506878jobem4404_7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Motivation, Attraction, and Parasocial Interaction on Talk Radio listening

Abstract: We examined the impact of motivation, interpersonal attraction, and parasocial interaction (PSI) on listening to public affairs talk radio. Hierarchical regression identified several results. PSI and exciting entertainment motivation predicted intentional and frequent listening to a favorite host. PSI, task attraction, and information motivation predicted regarding a host as an important source of information. PSI, information motivation, task attraction, and pass timdhabit motivation predicted

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
127
1
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(152 citation statements)
references
References 21 publications
(40 reference statements)
3
127
1
7
Order By: Relevance
“…As a new form of social interaction created by mass media, parasocial interaction is a pseudo-intimate relationship between the audience and media personalities such as talk radio hosts and TV shopping program hosts (Rubin & Step, 2000). A viewer forms an opinion about media personas based on the behavior of the media figures that appear in TV programs and talk shows, and his or her feeling is influenced by this opinion (Alperstein, 1991).…”
Section: Parasocial Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a new form of social interaction created by mass media, parasocial interaction is a pseudo-intimate relationship between the audience and media personalities such as talk radio hosts and TV shopping program hosts (Rubin & Step, 2000). A viewer forms an opinion about media personas based on the behavior of the media figures that appear in TV programs and talk shows, and his or her feeling is influenced by this opinion (Alperstein, 1991).…”
Section: Parasocial Interactionmentioning
confidence: 99%
“…With repeated parasocial encounters, the viewer of a TV program experiences a feeling of intimacy with the host to the extent that his or her attitudes and behaviors may change. For instance, Rubin and Step (2000) found that parasocial interaction with a talk radio host affected listeners' attitudes and behaviors on societal issues. Grant, Guthrie, and Ball-Rokeach (1991), who identified parasocial interaction as one of the key features of TV shopping, argued that shopping programs give viewers a sense of "being there" by airing live.…”
Section: Parasocial Interactionmentioning
confidence: 99%
“…Se cree que puede producir reacciones emocionales más intensas (Tamborini, Stiff, & Heidel, 1990), incrementar la atención y el recuerdo de la historia (Maccoby & Wilson, 1957), provocar una superior intención de adopción de los puntos de vista del personaje (Rubin & Step, 2000) y determinar el propio impacto del mensaje (Basil, 1996). Generalmente se acepta que en el proceso de identificación, los receptores evalúan los comportamientos de los personajes a partir de sus propias experiencias y que, por eso, mantienen una disposición positiva hacia aquellos personajes que se les parecen o que les recuerdan experiencias positivas de su vida y disposiciones negativas hacia los que no se les parecen o les recuerdan malas experiencias pasadas (Zilmman, 1991;Raney, 2003Raney, , 2004.…”
Section: La Identificación Con Los Personajesunclassified
“…Se cree que puede producir reacciones emocionales más intensas (Tamborini, Stiff, & Heidel, 1990), incrementar la atención y el recuerdo de la historia (Maccoby & Wilson, 1957), provocar una superior intención de adopción de los puntos de vista del personaje (Rubin & Step, 2000) y determinar el propio impacto del mensaje (Basil, 1996).…”
Section: La Identificación Con Los Personajesunclassified
“…First, 'interactivity' claims for real and observable interactions among humans via a machine or between man and machine, and thus implies real human behavior. Intra-personal processes, as described for example within the phenomenon of para-social interaction (e. g., Horton and Wohl, 1956;Rubin and Step, 2000), insufficiently constitute interactivity. Second, in case of interactivity a technical component occupies a key position within the communication process (Carey, 1989;Brody, 1990).…”
Section: From Interaction To Interactivitymentioning
confidence: 99%